Book review: Contra los zombis: Economía política y la lucha por un futuro mejor de Paul Krugman - Arias-Sosa, María Jesús (2023)
This book review presents the main topics covered in the book Arguing with zombies" by Paul Krugman, which compiles some of the articles published by the author throughout his professional career. From his critical approach to several negative ideas coonected to problems in the international economy in fields such as politics, tax reforms and action against climate change. This review links these thematic areas with the discipline of international trade and business.